2002
DOI: 10.1046/j.1365-8711.2002.05302.x
|View full text |Cite
|
Sign up to set email alerts
|

How is the reionization epoch defined?

Abstract: We study the effect of a prolonged epoch of reionization on the angular power spectrum of the cosmic microwave background. Typically reionization studies assume a sudden phase transition, with the intergalactic gas moving from a fully neutral to a fully ionized state at a fixed redshift. Such models are at odds, however, with detailed investigations of reionization, which favour a more extended transition. We have modified the code cmbfast to allow the treatment of more realistic reionization histories and app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…Kaplinghat et al (2003) modeled a two-step reionization, while Holder et al (2003) simulated reionization histories based on physical models of formation and evolution of the first ionizing sources. At variance with the double reionization model by Cen (2003) and with models considered here, almost all models discussed in these works display a monotonic increase of the ionized fraction with time.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Kaplinghat et al (2003) modeled a two-step reionization, while Holder et al (2003) simulated reionization histories based on physical models of formation and evolution of the first ionizing sources. At variance with the double reionization model by Cen (2003) and with models considered here, almost all models discussed in these works display a monotonic increase of the ionized fraction with time.…”
Section: Introductionmentioning
confidence: 75%
“…A similar 2-step reionization was also schematically considered by Kaplinghat et al (2003), for its effects on CMB. Still different reionization patterns were treated by Bruscoli et al (2002), Hu & Holder (2003 ), Naselsky & Chiang (2004) and Colombo (2004), confirming the interest in the relation between CMB data and early reionization, although often specifying no link with early object formation models. The present work is based on the dependence of the low-l behavior of the C E l spectra on the whole reionization history, and aims to predict the actual detectability of τ, as well as of the reionization redshift(s), the ionization rate(s), etc., with data on large angular scales.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Attempts to do so can result in biases and conflicting results. For example, using an ionization history derived from a particular numerical prescription [5] it was found that the partially ionized epoch was undetectable in the CMB, while analyses using semi-analytic models [6,7] showed that the predicted multiple epochs of reionization and partial recombination can be detected [8,9]. As another example, by assuming an overly simplistic step function model for reionization, the total optical depth τ in the semi-analytic models can be mis-estimated by up to a few 10 −2 [9]; while not a large amount it is already approaching the statistical errors in the first year WMAP data.…”
Section: Introductionmentioning
confidence: 99%